2000
DOI: 10.1093/humrep/15.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of spermatogenesis and successful conception after bone marrow transplant for acute leukaemia: Case report

Abstract: A case is presented of a young adult male diagnosed with acute myeloid leukaemia who was treated with busulphan and cyclophosphamide, but not total body irradiation, with subsequent bone marrow transplantation. After surviving for 5 years, he and his wife experienced a period of infertility. Interestingly, the problem was found to be with the female partner and the man's sperm evaluation seemed normal. A successful pregnancy ensued following the surgical removal of a large endometrioma and treating a luteal ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…Seven men established paternity after spontaneous recovery of natural fertility [2][3][4] and one achieved paternity with the use of assisted reproduction (ART). 5 We present two novel cases of biological paternity using testis sperm and assisted reproduction in men without sperm in the ejaculate (azoospermia) after BMT for hematologic malignancies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Seven men established paternity after spontaneous recovery of natural fertility [2][3][4] and one achieved paternity with the use of assisted reproduction (ART). 5 We present two novel cases of biological paternity using testis sperm and assisted reproduction in men without sperm in the ejaculate (azoospermia) after BMT for hematologic malignancies.…”
mentioning
confidence: 99%
“…8 Recovery of spermatogenesis after BMT, as measured by finding sperm in the ejaculate, varies widely in the literature with a range of 0-83% in small case series (Table 1). Although rare, spontaneous pregnancies have also been reported, [1][2][3][4] albeit generally not confirmed with paternity testing. In general, the return of sperm to the ejaculate varies with the type, dose and duration of the conditioning regimen, 9 and recent literature suggests that the return of sperm can occur from 1 to 9 years post BMT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…En altas dosis causa una severa supresión de las células de médula ósea, causando una prolongada mielosupresión afectando directamente las células con alto índice (Jopling y Rosendaal, 2001;Check et al, 2000). En nuestro estudio una simple dosis de Busulfán en ratones afectaría también a las espermatogonias en el sistema reproductor masculino.…”
Section: Discussionunclassified
“…2 While few cases of successful conception or spermatogenic recovery after HSCT, with chemotherapy alone, or combined with TBI conditioning, have been reported 1, [3][4][5][6][7][8][9][10][11][12] (Table 1), other studies assessing male fertility after HSCT have not reported any conception, highlighting the increased risk of altered reproductive function after HSCT. In 2010, the patient was still in complete remission.…”
Section: Dear Editormentioning
confidence: 99%